2006
DOI: 10.1155/2006/950682
|View full text |Cite
|
Sign up to set email alerts
|

Vision Influence on Whole‐Body Human Vibration Comfort Levels

Abstract: The well being of people needs to be a priority in the modern world. In that respect, vibration cannot be one more cause of stress. Besides that, vibration comfort is very important, since high levels may cause health or even tasks' accomplishment problems. Several parameters may influence the levels of vibration a human being supports. Among them, one can mention the influence of gender, age, corporeal mass index (CMI), temperature, humor, anxiety, hearing, posture, vision, etc. The first three parameters men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Hence, there is an increment of the Power Spectral Density when dolphin is closer to the patient, and thus a certain resonance frequency is yielded in specific parts of the patient's body (see Table I). Therefore, the main issue is that dolphin's sonar produces resonance of different parts of the human body, yielding effects on the nervous system of the patient via psychological changes [33]. This process is attributed to the generation of endorphin in the brain, bringing about the activation of collagen molecules throughout the body.…”
Section: Stimulimentioning
confidence: 99%
“…Hence, there is an increment of the Power Spectral Density when dolphin is closer to the patient, and thus a certain resonance frequency is yielded in specific parts of the patient's body (see Table I). Therefore, the main issue is that dolphin's sonar produces resonance of different parts of the human body, yielding effects on the nervous system of the patient via psychological changes [33]. This process is attributed to the generation of endorphin in the brain, bringing about the activation of collagen molecules throughout the body.…”
Section: Stimulimentioning
confidence: 99%
“…Although some have published values for resonance frequencies of various body parts (e.g., Duarte & Pereira, 2006), meaning those frequencies where the body shows the greatest response to a force input, others have considered the variables of transmissibility, energy absorption (or absorbed power), apparent mass, and impedance to be more indicative of how the body will respond to a given vibration in a given context Lundström, Holmlund, & Lindberg, 1998;Matsumoto & Griffin, 1998;Paddan & Griffin, 1998). In general, this latter group of measures bases analyses on empirical measurements of the motion input as well as the kinematics of the resulting body motion, thus accounting for any filtering-type effects that the body has on force input.…”
Section: Organism Constraintsmentioning
confidence: 99%
“…Although less information is currently available to characterize a broad spectrum of individuals across variations in race, gender, and age, some values have been published to provide at least a reference for the general order of magnitude. Table 2 provides some of these values, indicating resonance frequencies for individual upper body segments as published by Duarte and Pereira (2006). Note the general relationship between body segment size and the resonant frequency.…”
Section: Organism Constraintsmentioning
confidence: 99%
“…The dynamic interactions between the components of railway tracks influence the structural integrity of the track and the levels of noise and vibrations transmitted to buildings in proximity. Several studies have shown that such vibrations have significant effects on human health and comfort [1][2][3][4]. Railway-induced vibrations can also damage sensitive equipment [5,6] and historical buildings [7].…”
mentioning
confidence: 99%